Cover Image. (26th November 2018) - Ma, Mingliang; Yang, Yuying; Feng, Renjun; Jia, Li; Chen, Guopeng; Li, Wenting; Lyu, Ping
Abstract : The cover image is based on the Full Paper Preparation and characterization of magnetic hollow Fe3O4/P(GMA‐EGDMA)‐SO3H/Au‐PPy recyclable catalyst for catalytic reduction of 4‐nitrophenol by Na An et al., https://doi.org/10.1002/aoc.4739 .